Adding customer value in service quality in automotive assemble company / Muslihah Mustafa Ferkeri - Mustafa Ferkeri, Muslihah (Faculty of Business and Management, 2007)
This research has been conducted for the purpose of "adding customer value in service quality in automotive assemble company". In this research, the main problem is that the company only receives a small increment in terms of profit every year even though they receive a lot of projects from their customers.